S.P.A.R.K. THE TALK: A PLAY TO PERFORMANCE MODEL FOR TEACHING ENGLISH IN FOOD AND BEVERAGE SERVICE - Ni Putu Dianita Safitri; Nirmala Tari (e-Journal of ELTS (English Language Teaching Society), 2026)
ABSTRACT   This study used a mixed-methods research design to examine the implementation of the S.P.A.R.K. model (Social Media Videos, Play through Online and Offline Games, Active Role Play, Realistic Scenarios, and Knowledge Building) in a Food and Beverage Service English course. The study involved 12 first-semester students in the Diploma I Food and Beverage Service program and was conducted over 16 class meetings. The S.P.A.R.K. model combines online and offline games, social media videos, and role-play activities to help students practice English in authentic hospitality situations. Data were collected through pre-test and post-test speaking assessments and a questionnaire consisting of closed-ended and open-ended questions. Quantitative data were analyzed using descriptive statistics, while qualitative data were analyzed descriptively based on students' responses to the open-ended questionnaire. The results showed that students improved their speaking performance, although only a small improvement in fluency was observed. Students also reported high levels of motivation, engagement, and confidence. They found the combination of games, social media videos, and role-play activities enjoyable and helpful for learning English. These findings suggest that the S.P.A.R.K. model creates an engaging learning environment and supports the development of students' English communication skills. However, a longer period of practice may be needed to achieve greater improvement in speaking fluency.